Governing on Implementation of REDD+ Project: Case Study of Berbak Landscape - Teis Nuraini; Yeremias Torontuan Keban (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2018)
Following the result of the United Nations Framework Convention on Climate Change in 2007, Indonesia implemented reducing emissions from deforestation and forest degradation, conserving and enhancing forest carbon stocks and sustainably managing forests (REDD+). One of the collaborative REDD+ projects in Indonesia is the Berbak landscape REDD+ Program, initiated by the Zoological Society of London (ZSL). The project is divided into two phases of implementation, as of 2018, has gone through both phases. However, the project has only fulfilled 20% of its targeted program despite being in the final year of implementation. Addressing this issue, this study attempts to look at the governance in the project to understand what constitutes the governance of Berbak landscape REDD+ program and how governance determines its implementation landscape. The study employs a qualitative approach. In addition, it follows four governance indicators developed by Ostrom (1990): coordination, reporting, bureaucracy, and monitoring. Based on the data analysis, it is found that the project has diverse stakeholders with different connections and authority and good governance plays a big role in determining the successful implementation of the project. Thus, it is important to develop good governance to find a better solution for the challenges faced by the project. Keywords: REDD+, Berbak landscape, Governance